2009
DOI: 10.1186/1471-2164-10-527
|View full text |Cite
|
Sign up to set email alerts
|

Target gene approaches: Gene expression in Daphnia magna exposed to predator-borne kairomones or to microcystin-producing and microcystin-free Microcystis aeruginosa

Abstract: BackgroundTwo major biological stressors of freshwater zooplankton of the genus Daphnia are predation and fluctuations in food quality. Here we use kairomones released from a planktivorous fish (Leucaspius delineatus) and from an invertebrate predator (larvae of Chaoborus flavicans) to simulate predation pressure; a microcystin-producing culture of the cyanobacterium Microcystis aeruginosa and a microcystin-deficient mutant are used to investigate effects of low food quality. Real-time quantitative polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 34 publications
6
75
3
Order By: Relevance
“…There have been concerns using only one reference gene when establishing a normalization factor. However, Schwarzenberger et al (2009) showed recently that the transcription level of actin was not substantially changed in Daphnia magna Straus challenged by predator cues or natural xenobiotics, although changes on the corresponding protein level occurred. Also our data ( Fig.…”
Section: Selection Of Genesmentioning
confidence: 99%
“…There have been concerns using only one reference gene when establishing a normalization factor. However, Schwarzenberger et al (2009) showed recently that the transcription level of actin was not substantially changed in Daphnia magna Straus challenged by predator cues or natural xenobiotics, although changes on the corresponding protein level occurred. Also our data ( Fig.…”
Section: Selection Of Genesmentioning
confidence: 99%
“…Again, much work on identifying genes that control predator odour-induced plasticity has involved Daphnia pulex, in which the eco-responsive genome has been sequenced (Colbourne et al, 2011). In the related species Daphnia magna, exposure to fish predator odour results in the upregulation of cyclophilin (Dappu-92663), a gene involved in protein folding, while exposure to an invertebrate predator leads to downregulation of the same gene (Schwarzenberger et al, 2009). While this differential expression may reflect different life-history responses to different predators, it is unclear how cyclophilin mediates the expression of these different traits.…”
Section: Genetic Responsesmentioning
confidence: 99%
“…These genes code for enzymes involved in glycolysis, protein catabolism and the tricarboxylic acid cycle. Notably, all three belong to expanded gene families that result from ancestral gene duplications [67].…”
Section: Linking Genes To Ecologically Relevant Trait Variationmentioning
confidence: 99%